Design of a Troubleshooting Digital Test Bench for the Beechcraft King C-90, 200, B200, 300 and 350 Aircraft GCU - Cabrera Arias, Carlos Arturo; Garay Rairan, Fabian Steven; Arango Calderón, Ingrid; Gómez Vargas, Óscar Edilson (Ingeniería, 2020)
Context: The Colombian Army’s First Aircraft Maintenance Battalion must periodically test the performance of Generator Control Unit (GCU) on its Beechcraft King Air aircraft, which compels the operator to assume uncomfortable and non-ergonomic physical positions. This article proposes the use of a portable digital troubleshooting test bench for these units that facilitates the taking of measurements, the interpretation of the acquired information, and the technical reports. Method: The Integrate, Innovation, Process model (IIP) for the development of aviation technology innovation projects was used to design the test bench. Then, its functional modules were defined, and voltage and impedance measurement devices, an internal report storage system, and the user interface were included. Tests were conducted together with technical operators on the available Beechcraft King C-90, 200, B 200, 300, and 350 series aircraft. Finally, a technical report was elaborated to validate the test bench results. Results: The number of operators required to carry out the tests was reduced from four to one. The digital test bench only requires the connection of measurement harnesses by the operator, so it allows an improvement in ergonomics for the personnel. Using the bench, the review and evaluation time of the GCU was reduced from 120 minutes to 26 minutes, which implies an 86,66% decrease in fuel consumption. Conclusions: By using the digital troubleshooting test bench, the number of operators needed and the checkup and assessment times of the GCU were reduced, which means a decrease in fuel expenses. Its ease of transportation allows aircraft to be checked outside the Maintenance Battalion hangars, but the implementation of a USB port to store the reports should be considered. Acknowledgments: We would like to thank the First Aircraft Maintenance Battalion of the Colombian National Army and the Aviation School for their contribution to the development of the prototype. This project was funded by the National Army of Colombia, Science of Science and Technology, under internal code No. 118315.